Sintesis Dan Karakterisasi Urea-Hidroksiapatit Dengan Variasi Ca(OH)2 Sebagai Kandidat Pupuk Lepas Lambat - Syahiful Hadi; Suryajaya Suryajaya; Abdullah Abdullah; Kissinger Kissinger (EnviroScienteae, 2019)
Urea-hydroxyapatite can be used as fertilizer which was efficient and environmentally friendly. The variation of Ca(OH)2 in the urea-hydroxyapatite’s synthesis and its characterization would provide information for manufacturing slow release fertilizer. The material used were urea (99.5 %); Ca(OH)2; H3PO4 0.67 M and distilled water. The synthesis technique used in this study is bottom-up with Ca(OH)2 variation of 6, 8, 10 and 12 grams. The results of the synthesis with 6 grams of Ca(OH)2  was not able to produce sediment powder. The results of the Scanning Electron Microscopy (SEM) showed that the urea packaging with hydroxyapatite was better for variations of Ca(OH)2  8 grams and 10 grams. The results of the Energy Dispersive X-Ray Spectrometry (EDX) showed more elemental composition in the variation of Ca(OH)2  8 grams and 10 grams which were 35.7 Wt% and 40.4 Wt%. The results of the Fourier Transform Infrared Spectrometer (FTIR) showed that the variation of Ca(OH)2  8 gram has a good bonding of urea and hydroxyapatite. The Particle Size Analyzer (PSA) measurement for all samples of urea-hydroxyapatite yielded the particle size of about 0.5–2.5 mm and 10–15 mm for urea and hydroxyapatite, respectively. As a conclusion, the variation of Ca(OH)2  8 grams could be recommended as a reference in the composition of urea-hydroxyapatite fabrication for slow release fertilizer.